Conscious intelligence is overrated: The normative unconscious and hypnosis. Issue 4 (1st April 2022) - Weinberger, Joel; Brigante, Mathew; Nissen, Kevin
ABSTRACT: Hypnosis has been mysterious and controversial for hundreds of years. The legacy of this history is still with us. The philosophy of Ryle and of Dennett argue that the usual emphasis placed on states of consciousness and privileged access is misplaced. Cognitive neuroscience supports this by showing that unconscious processes explain much of our functioning and that what we call consciousness and privileged access is illusory. Attribution theory can largely account for the subjective states that have been seen as characteristic of and unique to hypnosis. Current models of hypnosis are reviewed and shown to have maintained classic and outdated views of dissociation and/or disconnected executive systems. Normative unconscious processes can account for much of hypnotic phenomena thereby showing hypnosis to be a normative phenomenon. An unconscious need to be absorbed into or become part of something beyond the self may underlie some of the individual differences in hypnotizability.